Experimental Study on Nonlinear Motion Characteristics of Clean and Biofouling Aquaculture Cage Array in Waves - Changfeng Tian; Huang Liu; Mingchao Cui; Shouqi Cao; Zhijing Xu (Journal of Marine Science and Engineering)
This paper aimed to understand the nonlinear dynamic responses that arise from the interaction between waves and a biofouling aquaculture cage array. To that end, physical model tests of a biofouling aquaculture cage array in a 1 <semantics>×</semantics> 3 configuration in regular waves were conducted. Wave steepness values of 1/60, 1/30, and 1/15 were considered within the frequencies spanning from low- to high-frequency bands. Then, the nonlinear dynamic responses of the system were systematically decomposed into four successive orders of components. This approach allowed for a thorough assessment of the inherent nonlinearity within the biofouling system by analyzing each individual order. The results highlight that the first-order harmonic component was the predominant contributor influencing the nonlinear dynamic response, while the higher-order harmonic components remained crucial in their contribution to the overall nonlinear dynamic response of the system. In particular, the harmonics within the low-frequency regime exhibited significantly greater nonlinearity compared with those in the high-frequency regime. A notable decrease in the amplitude of the harmonic component could be identified in the low-frequency regime due to the damping from the biofouling. The comprehensive analysis of the nonlinear dynamics within the biofouling system provides insights into optimizing the performance of aquaculture systems.